Ion Exchange Behavior of Polypyrrole Doped with Large Anions in Electrolytes Containing Mono‐ and Divalent Mmetal Ions. Issue 4 (18th February 2013) - Latonen, Rose‐Marie; Akieh, Marceline N.; Vavra, Kevin; Bobacka, Johan; Ivaska, Ari
Abstract Electrochemical Quartz Crystal Microbalance was used to investigate the ion exchange behavior of polypyrrole (PPy) films doped with multicharged sulfated β‐cyclodextrin (βCD) or 4‐sulfonic calix[6]arene (C6S) immersed in 0.1 M KNO3, Ca(NO3)2 and Mn(NO3)2. The PPy films showed mixed ion exchange behavior in KNO3 and Ca(NO3)2 solutions, but the ion exchange behavior was more cationic in Mn(NO3)2. In all cases, ion pair formation was observed between cations from the electrolyte and the negatively charged sulfonate groups of the dopant anions. It was also observed that the PPy films became more swollen in Mn(NO3)2 solution than in the other electrolytes.